Building RESTful Python web services create web services that are lightweight, maintainable, scalable, and secure using the best tools and techniques designed for Python - Hillar, Gastón C. (Packt, 2016)
Annotation
Includes index. - Online resource; title from PDF title page (EBSCO, viewed November 17, 2016)
Keywords: Application program interfaces (Computer software); Web sites -- Design; Python (Computer program language); Interfaces de programmation d'applications; Sites Web; Conception; Python (Langage de programmation); APIs (interfaces); COMPUTERS; Programming; General; COMPUTERS; Programming Languages; General; Web sites; Design